THE USE OF SHORT STORIES TO INCREASE EIGHTTH-GRADE STUDENTS’ READING COMPREHENSION AT SMP NEGERI 1 BOLAANG - Novita Lawitang; Fivy A. Andries; Rinny S. Rorimpandey (SoCul: International Journal of Research in Social Cultural Issues, 2022)
Reading comprehension is a part of English language learning in Indonesia since the students, based on the Kurikulum 2013, are required to learn and read many kinds of texts. This research aims to investigate the effectiveness of the use of short stories in enhancing students’ reading comprehension. This study is conducted using the quantitative approach with a pre-experimental design (one group pre-posttests design). The pre-posttests are used to obtain data related to students’ reading comprehension. Those tests consist of 10 questions that are generated from two texts prepared by the researchers. 36 eighth-grade students at SMP Negeri 1 Bolaang are the object of this study. The data is then analyzed using the mean score formula and standard deviation formula. The findings show that the mean score of the pre-test is 4.4, and the standard deviation is 1.5. Meanwhile, the mean score of the post-test is 5.6, and the standard deviation of the post-test is 1.6. It indicates that students’ reading performance in the post-test is better than their performance before the treatment (pre-test). So, it is concluded that short stories are an effective technique to be used in increasing students’ reading comprehension. Teachers of English at junior high school are recommended to use short stories in teaching reading comprehension to help students understand the reading materials.